Evidence of potential impacts of a nutrition-sensitive agroecology program in Andhra Pradesh, India, on dietary diversity, nutritional status, and child development - Ch, Lakshmi Durga; Bharath, Yandrapu; Bliznashka, Lilia; T., Vijay Kumar; Jonnala, Veerendra; Chekka, Vijayalakshmi; Yebushi, Srileka; Roy, Aditi; Venkateshmurthy, Nikhil Srinivasapura; Prabhakaran, Poornima; Jaacks, Lindsay M. (2024)
Introduction While a number of studies have examined the nutritional impacts of agroecological interventions, few have examined impacts on child development, maternal and child anemia, and men’s dietary diversity. Moreover, there have been few such evaluations at scale. We evaluated the impact of a large-scale, multi-component food-based nutrition intervention involving homestead food production, nutrition counselling, cooking demonstrations, and crop planning exercises.